DEVELOPING STUDENTS PROFESSIONALLY SIGNIFICANT SKILLS IN EDUCATIONAL PROGRAMMES AT NON-LINGUISTIC FACULTIES - Druzhinina, Rimma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article addresses some aspects of students’ extracurricular activities in foreign language teaching at non-linguistic faculties. The topicality of our study consists in insufficient number of scientific works on extracurricular activities and insufficient application of students’ extracurricular activities in foreign language teaching as a means of facilitating students' professionally significant communicative potential. The study focuses on the issues of students’ communicative training through extracurricular activities in foreign language teaching at faculties of management. Hence the goal of our study is to provide theoretical justification and methodological development of the concept of extracurricular activities in foreign language teaching as a means of facilitating communicative training. We have examined the essence and have presented a definition of extracurricular activities in foreign language teaching. We have elaborated a concept and examined components and characteristics of extracurricular activities in foreign language teaching. We have produced a model for extracurricular activities and identified its stages, algorithms and communicative training indicators. The conceptual framework of the study follows the model of professional competence approach. Research and experience data obtained in our experiential work make it possible to identify the significance of extracurricular activities in foreign languages for students’ professional development in educational programs at faculties of management.